214k views
4 votes
Hello math olzzzzzzz

Hello math olzzzzzzz-example-1

1 Answer

5 votes

Answer:

Checkmark:

✓ The sequence is geometric

✓ The recursive formula for the sequence is
An = A_(n-1)(-3);
A_(1) =-2

✓ The explicit formula for the sequence is
t_(n) = (-2) (-3)^(n-1)

Explanation:

This is a geometric sequence since there is a common ratio between each term. In this case, multiplying the previous term in the sequence by -3 gives the next term.

r = -3


t_(n) = t_(1) r^(n-1)


t_(1) = -2

Substitute the values in the equation:


t_(n) = (-2) (-3)^(n-1)

This is a explicit formula since the next value depends on the position of n (1, 2, 3 .etc)

The recursive formula would be:


An = A_(n-1)(-3)

Checkmark:

✓ The sequence is geometric

✓ The recursive formula for the sequence is
An = A_(n-1)(-3);
A_(1) =-2

✓ The explicit formula for the sequence is
t_(n) = (-2) (-3)^(n-1)

User Xaa
by
5.1k points